Method of construction synthetic field / Ain Nurul Ashikin Abdul Rasid - Abdul Rasid, Ain Nurul Ashikin (Universiti Teknologi Mara, Perak, 2014)
In Malaysia synthetic field is not widely known. The synthetic field only install at stadium or any huge field. It is because the artificial turf is very expensive. The artificial turf can comes from any size for examples 2"x2". This size only can use at small placed but if for installation synthetic field it will comes in roll carpet and the long is 65m. There is no supply the artificial turf in Malaysia. Our country does not have the expertise in construction field. We must get an expertise in installation synthetic field during installation and we can get any information for maintenance of the synthetic field. The installation of artificial turf is using technique gluing. The artificial turf will placed after quarry dust is complete. The glue that used for gluing the artificial turf is very specific glue and do not have at Malaysia. After the installation and accessories at the field is complete, the supplier of the artificial turf will do a test. The test called FIFA Test. The test is to make sure the artificial turf that they supply is perfect and do not have a defect. Second, the supplier wants this synthetic field is follow the standard synthetic field with another country. Lastly is, the supplier wants to make sure this synthetic field is safety to use to people. The conclusion is, our country can make a different and decrease the cost in maintenance of field for the future even we does not have any expertise in installation synthetic field. The recommendation is, our country can order artificial turf from the others country for examples China for installation of synthetic field.